Visual programming language environment for different IoT and robotics platforms in computer science education. Issue 2 (1st June 2018) - De Luca, Gennaro; Li, Zhongtao; Mian, Sami; Chen, Yinong
Abstract : This study presents the authors' recent research and application of a new visual programming language and its development environment: VIPLE (Visual IoT/Robotics Programming Language Environment) at Arizona State University (ASU). ASU VIPLE supports a variety of IoT devices and robots based on an open architecture. Based on computational thinking, VIPLE supports the integration of engineering design process, workflow, fundamental programming concepts, control flow, parallel computing, event‐driven programming, and service‐oriented computing seamlessly into a wide range of curricula, such as introduction to computing, introduction to engineering, service‐oriented computing, and software integration. It is actively used at ASU in several sections of FSE 100: Introduction to Engineering and in CSE 446: Software Integration and Engineering, as well as in several other universities worldwide.